2018
DOI: 10.7326/m17-3365
|View full text |Cite
|
Sign up to set email alerts
|

High-Deductible Insurance and Delay in Care for the Macrovascular Complications of Diabetes

Abstract: Background: Little is known about the long-term effects of high-deductible insurance on care for chronic medical conditions. Objective: To determine whether a transition from low-deductible to high-deductible insurance is associated with delayed medical care for macrovascular complications of diabetes. Design: Observational longitudinal comparison of matched groups. Setting: A large national health insurer during 2003 to 2012. Participants: The intervention group comprised 33 957 persons with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
(32 reference statements)
0
57
1
Order By: Relevance
“…In recent years, there has been growing enrollment in high-deductible health plans (HDHPs) among working age adults [ 16 ]. For vulnerable populations, especially low-income patients, HDHPs may present barriers to care and increases in adverse outcomes and costs [ 17 ]. Wharam et al showed that low-income people with diabetes and HDHPs had increased high severity emergency department visits and hospitalizations compared to the general population with diabetes on HDHPs [ 17 ].…”
Section: Economic Vulnerabilitymentioning
confidence: 99%
“…In recent years, there has been growing enrollment in high-deductible health plans (HDHPs) among working age adults [ 16 ]. For vulnerable populations, especially low-income patients, HDHPs may present barriers to care and increases in adverse outcomes and costs [ 17 ]. Wharam et al showed that low-income people with diabetes and HDHPs had increased high severity emergency department visits and hospitalizations compared to the general population with diabetes on HDHPs [ 17 ].…”
Section: Economic Vulnerabilitymentioning
confidence: 99%
“…SDC Section 1: Imputation of deductible amounts Our algorithm for imputing employer-mandated membership in high deductible health plans has been described in detail previously. [1][2][3] We summarize these methods briefly below.…”
Section: Supplemental Digital Content (Sdc)mentioning
confidence: 99%
“…Our dataset contains limited and incomplete individual-level socioeconomic variables; to derive proxy measures, 8 our data vendor converted members' most recent residential street addresses to geocodes which can be linked to publicly available geographically-derived socioeconomic measures. Geographic measures of socioeconomic status have been validated [9][10][11] and used in multiple studies by ourselves 3,12,13 and others 14,15 to examine the differential impact of changes in cost-sharing within population subgroups. We linked to census tract-level data from the 2008-2012 American Community Survey (ACS) 16 ,17 to create measures of neighborhood poverty, defined as <5%, 5.0-9.9%, 10.0-24.9%, ≥25.0% of households living below the US Department of Health and Human Services federal poverty threshold, 18 which we stratified for subgroup analysis as lower income (<10.0%) vs. higher income (≥10.0%).…”
Section: Sdc Section 5: Definitions Of Covariatesmentioning
confidence: 99%
See 2 more Smart Citations